IMPLEMENTASI CUSTOMER-BASED BRAND EQUITY MODEL DALAM MENINGKATKAN PEMANFAATAN PELAYANAN KESEHATAN DI PUSKESMAS SUNGAI RAMBUTAN, KABUPATEN OGAN ILIR, 2011 - Budi, Iwan Stia; Faisya, A. Fickry (FKM - UNEJ, 2012)
Purpose of study was formulate recommendation to improving the utilization of Sungai Rambutan Public Health Center through Customer-Based Brand Equity Model. This study used descriptive study. Result : Brand awareness about sungai rambutan: Sungai Rambutan public health center as free health services, health services Â no reliable, no guarantee of healing, infrastructure incomplete ,the discipline of work Â less and not had willingness to visit sungai rambutan public health center if they were sick.